Fashioning masculinity : national identity and language in the eighteenth century - Cohen, Michèle, 1944- (Routledge, 1996)
The fashioning of English gentlemen in the eighteenth century was modelled on French practices of sociability and conversation. Michele Cohen shows how at the same time, the English constructed their cultural relations with the French as relations of seduction and desire. She argues that this produced anxiety on the part of the English over the effect of French practices on English masculinity and the virtue of English women. By the end of the century, representing the French as an effeminate other was integral to the forging of English, masculine national identity. Michele Cohen examines the.